PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS CHIEVEMENT DIVISION) BERBASIS ICT (INFORMATION AND COMMUNICATIONS TECHNOLOGIES) - Iryana Muhammad; Hayatun Nufus; Mursalin Mursalin (Jurnal Kajian Pembelajaran Matematika, 2017)
This study aims to improve one of the objectives of mathematics learning, namely the ability of mathematical communication through the application of cooperative learning type STAD (Student Teams Achievement Division) based on ICT (Information and Communications Technologies) using Autograph Software in Statistics Course. The approach used in this study is a quantitative approach to the type of quasi-experimental research. The study was conducted in the academic year 2016/2017. The population is all students of Mathematics Education Study Program of the Faculty of Teacher Training and Education Universitas Malikussaleh, and all students of Mathematics Education Study Program of the Faculty of Tarbiyah of the IAIN Malikussaleh Lhokseumawe are 80 students. Sampling technique by purposive sampling. Based on the results obtained that the value of F for learning factors of 4.451 with a significance of 0.038 smaller than the significance level of 0.05. Therefore, there is an increase in mathematical communication skills of mathematics education students through the application of cooperative learning type STAD by using Autograph Software on Statistics course. Then it can be concluded that the improvement of mathematical communication skills by using Autograph Software better than without using Autograph Software.Keywords: mathematical communication, cooperative learning type STAD, autograph software